The Dream of Bandung and the UN Treaty on the Prohibition of Nuclear Weapons. Issue 1 (2nd January 2019) - Intondi, Vincent
ABSTRACT: From nuclear weapons testing to uranium mining and from the actual use of nuclear weapons to the mere threat of use, race, colonialism and nuclear weapons, all have been inextricably linked since 1945. One could argue that these links have never been clearer. Indeed, as much of the non-white world joins together to ban nuclear weapons, the United States and other nuclear-armed states ignore and boycott the Treaty on the Prohibition of Nuclear Weapons (TPNW). But the passage of the TPNW has shown what is possible when nations and committed individuals join together for peace, and while it did not abolish nuclear weapons, it has edged the world a bit closer to the dream set at the Bandung Conference: a world without racism, colonialism and nuclear weapons.